2014
DOI: 10.1007/s10544-014-9866-0
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-digital PCR: Enrichment and quantification of rare DNA variants

Abstract: Rare variant enrichment and quantification was achieved by allele-specific, competitive blocker, digital PCR for aiming to provide a noninvasive method for detecting rare DNA variants from circulating cells. The allele-specific blocking chemistry improves sensitivity and lowers assay cost over previously described digital PCR methods while the instrumentation allowed for rapid thermal cycling for faster turnaround time. Because the digital counting of the amplified variants occurs in the presence of many wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…4C). 116 The disc consisted of a central loading chamber in which the sample and oil phase were injected. It demonstrated that compartments were generated through chambers rather than droplets on a centrifugal platform.…”
Section: Integrated Systemsmentioning
confidence: 99%
“…4C). 116 The disc consisted of a central loading chamber in which the sample and oil phase were injected. It demonstrated that compartments were generated through chambers rather than droplets on a centrifugal platform.…”
Section: Integrated Systemsmentioning
confidence: 99%
“…Furthermore, a qualitative method based of the counts of positive PCRs can be applied (digital PCR). In accordance with a prior study, in which rare DNA variants were detected, this digital counting of PCR replicates with methylated ccfDNA can be called “quasi-digital PCR” [ 30 ]. On the basis of the distribution of positive and negative reactions, Poisson statistics can predict the amount of methylated ccfDNA in the sample [ 31 ].…”
Section: Introductionmentioning
confidence: 56%
“…As an example, droplet-based digital PCR enabled the precise determination of mutations in several cancer cell-lines and the precise quantification of a single mutated KRAS gene in a background of 200,000 unmutated KRAS genes (Pekin, et al, 2011). In a similar vein, BRAF mutation detection was accomplished using a spinning disk digital PCR layout ( Figure 2) (Sundberg, et al, 2014). In this case a polymer microfluidic system the size of a DVD was fabricated with a single spiral channel that contained 1000 microwells on the outside of the disc.…”
Section: Digital Pcrmentioning
confidence: 99%
“…(Inset) Post PCR fluorescent image of the disk.Fluorescence correlates to number of copies per well. Reprinted with permission from(Sundberg, et al, 2014). Copyright 2010 American Chemical Society.…”
mentioning
confidence: 99%